OGRANICZENIA SWOBODNEGO PRZEPŁYWU TOWARÓW I USŁUG ZE WZGLĘDU NA INTERES PUBLICZNY W ŚWIETLE ORZECZNICTWA EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI - (:unkn) unknown (Wydział Prawa i Administracji UAM, 2004)
The rules governing the free flow o f goods on the Community internal market, fundamental for full integration of the areas o f law necessary to achieve aims set by the Founding Treaties, have been included in the state order. Member States, however, can introduce and maintain legal measures limiting the free flow o f goods and services in consideration of public interest. The measures can only have limited scope due to the countries’ obligation to respect the purposefulness requirement and proportionality criteria. The European Court o f Justice determines (mainly in the form o f preliminary ruling procedures) the conditions required for the state to be able to invoke imperative requirements set out in the Treaty provisions and developed in precedence rulings without contradicting supranational objectives o f integration and rules governing the common frontier-free market. We can hardly overrate the Court’s interpretation work in determining accurately the referents o f the notion “public interest” and defining individual critria whose fulfilment is requisite for a member state to benefit from legal derogation from the free flow. In relation to Poland’s accesión to the European Union, discussion on “limits to the free flow of goods and services in the common market because of public interest in the light o f the European Court o f Justice’s decisions” can be found useful, particularly for legislative process and the practice of application of the state law.
LIMITS TO THE FREE FLOW OF GOODS AND SERVICES IN THE COMMON MARKET BECAUSE OF PUBLIC INTEREST IN THE LIGHT OF THE EUROPEAN COURT OF JUSTICE’S DECISIONS